Internationalization of the University of Maribor – Some Examples of Academic Cooperation in the International Environment - Tominc, Polona; Presker, Robert; Kraljić, Mladen; Zurc, Joca; Rijavec, Vesna; Krivograd, Jelena; Žnidaršič Mohorič, Anja; Gorjanc, Petra; Šprajc, Polona; Areh, Igor (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
The chapter on internationalization at the University of Maribor examines key strategies and achievements in the institution’s international collaboration over the decades. It highlights the transition from the university’s initial steps in the international academic sphere to the development of robust programmes such as Erasmus and CEEPUS, which have significantly enhanced student and staff mobility. The university places a strong emphasis on integrating international students and developing study programmes in foreign languages, thereby strengthening its global presence. Internationalization is fostered across all areas of the university’s operations, contributing to its academic excellence. The internationalization strategy, which incorporates intercultural content into the curriculum and enhances digital mobility, enables the University of Maribor to remain competitive and relevant in the dynamic global higher education and research landscape.